2007
DOI: 10.1104/pp.106.094532
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of an R1R2R3 MYB Gene, OsMYB3R-2, Increases Tolerance to Freezing, Drought, and Salt Stress in Transgenic Arabidopsis

Abstract: We used a cDNA microarray approach to monitor the expression profile of rice (Oryza sativa) under cold stress and identified 328 cold-regulated genes. Thirteen such genes encoding MYB, homeodomain, and zinc finger proteins with unknown functions showed a significant change in expression under 72-h cold stress. Among them, OsMYB3R-2 was selected for further study. Unlike most plant R2R3 MYB transcription factors, OsMYB3R-2 has three imperfect repeats in the DNA-binding domain, the same as in animal c-MYB protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
289
0
5

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 515 publications
(322 citation statements)
references
References 59 publications
13
289
0
5
Order By: Relevance
“…AtMyb41 from Arabidopsis is transcriptionally regulated in response to salinity, drought, cold, and ABA (Lippold et al, 2009 (Gigolashvili et al, 2007). In contrast, OsMYB3R-2 transgenic plants showed enhanced tolerance to freezing, drought and salt stress and decreased sensitivity to ABA (Dai et al, 2007). Different level of tolerance was imparted by overexpression of OsMYB4 depending on the nature of the host plants.…”
Section: Wwwintechopencommentioning
confidence: 99%
“…AtMyb41 from Arabidopsis is transcriptionally regulated in response to salinity, drought, cold, and ABA (Lippold et al, 2009 (Gigolashvili et al, 2007). In contrast, OsMYB3R-2 transgenic plants showed enhanced tolerance to freezing, drought and salt stress and decreased sensitivity to ABA (Dai et al, 2007). Different level of tolerance was imparted by overexpression of OsMYB4 depending on the nature of the host plants.…”
Section: Wwwintechopencommentioning
confidence: 99%
“…OsMYB3R-2 in rice transgenic plants enhanced tolerance to freezing, dehydration and salt stress and decreased sensitivity to ABA (Dai et al 2007). Similarly, El-kereamy et al (2012) studied the rice R2R3-MYB transcription factor OsMYB55 and concluded that overexpression of OsMYB55 improved rice plant tolerance to high temperature which was associated with enhanced amino acid metabolism through transcription activation.…”
Section: Abiotic Stressmentioning
confidence: 99%
“…The evidence for two transmembrane domains in the RCI2 protein family is still circumstantial (Nylander et al, 2001;Kroemer et al, 2004). response signaling (Nylander et al, 2001;Kroemer et al, 2004;Medina et al, 2005;Mitsuya et al, 2006;Dai et al, 2007). The gene possesses orthologs in a variety of plant species as well as three Pseudomonas species, Neurospora crassa, and Caenorhabditis elegans (Kroemer et al, 2004).…”
Section: Isolation Of Successful Transgenic Linesmentioning
confidence: 99%